Sosialisasi Manajemen Usaha untuk Pengembangan Ekonomi Keluarga pada Kelompok PKK Kelurahan Joyosuran Kecamatan Pasar Kliwon Surakarta - Rini Handayani (UIN Raden Mas Said Surakarta, 2020)
The needs of life are increasing nowadays causing people to try even harder to work or runtheir businesses. The income earned will later support the survival of the family. In developedcountries, family-based business activities are one solution to solving family economicproblems. Family-based micro business is expected to reduce dependence on job vacanciesneeded by a family, reduce poverty and improve family welfare. In addition, the potential forhousewives who play a role in the family economy to support family income needs efforts sothat family needs can be fulfilled. This community service activity is carried out on motherswho are members of the PKK RT 05 / RW 06 group of Joyosuran Village, Pasar KliwonSuarakarta District. The aim is to increase the insight and knowledge of the PKK mothersregarding various forms of business that can be done, financial management and marketing.Activities carried out on 15-16 May 2019 at. The results of the activity indicated that thematerial presented by the service team was aligned with the needs of these mothers. Thenumber of participants who met the expected targets showed a positive response from thePKK mothers to participate in this activity.